TRANSLATION PECULARITIES OF ELECTRICAL EQUIPMENT TERMS: SCHOLARLY ANALYSIS OF TRANSLATING STRATEGIES - Saliyeva Zarina; Mukhammedova Mohinur (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
The study aims to describe the strategies of electrical equipment terms in translation from English into the Uzbek language. The field of electrical engineering is characterized by the use of specialized terms and concepts. When translating these terms from English to Uzbek, several linguistic and technical challenges arise. This article explores the peculiarities involved in the translation process, focusing on the strategies used to maintain accuracy, clarity, and consistency. Key challenges include differences in technical terminologies, variations in language structure, and the need for contextual understanding. Solutions such as the creation of standardized glossaries and collaboration between linguists and engineers are proposed to improve the translation quality.